1999
DOI: 10.1017/s0007114599000811
|View full text |Cite
|
Sign up to set email alerts
|

The effect of intake on protein metabolism across splanchnic tissues in growing beef steers

Abstract: The contribution of the total splanchnic tissue (TSP; portal-drained viscera (PDV) plus liver) to whole-body protein metabolism was estimated in relation to intake (0·6, 1·0 and 1·6 × maintenance requirements), in six multicatheterized growing beef steers used in a double 3 × 3 Latin square design. At the end of each 21 d experimental period, [1-13C]leucine was infused into a jugular vein (1·05 mmol/h for 5 h, preceded by a priming dose of 1·05 mmol). Arterial, portal and hepatic blood samples were collected h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
24
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 34 publications
(71 reference statements)
8
24
0
Order By: Relevance
“…Given the importance of the liver in AA utilization and ureagenesis, it is most probably involved in the variations in the efficiency of N utilization in this study. Decreased growth and protein net retention in the LN and LE diets were also observed, similar to what was previously shown after a reduction of the amount of intake or energy intake (Calloway, 1975;Lapierre et al, 1999;Kraft et al, 2008). Concerning the impact of a decreased supply of N in the diet, either reduced N retention is observed (Bruckental et al, 1997, this study) or N retention is unaltered (Calloway, 1975;Castillo et al, 2001; Table 3.…”
Section: Discussionsupporting
confidence: 87%
“…Given the importance of the liver in AA utilization and ureagenesis, it is most probably involved in the variations in the efficiency of N utilization in this study. Decreased growth and protein net retention in the LN and LE diets were also observed, similar to what was previously shown after a reduction of the amount of intake or energy intake (Calloway, 1975;Lapierre et al, 1999;Kraft et al, 2008). Concerning the impact of a decreased supply of N in the diet, either reduced N retention is observed (Bruckental et al, 1997, this study) or N retention is unaltered (Calloway, 1975;Castillo et al, 2001; Table 3.…”
Section: Discussionsupporting
confidence: 87%
“…Whole body protein synthesis was close to those reported in sheep using the same experimental methods (Krishnamurti and Janssens 1988;Sano et al 2004), and was also similar to those in goats using the [ 2 H 5 ]phenylalanine model ). However, WBPS in sheep was considerably lower than growing steers (Lapierre et al 1999), even when the data was compared based on the metabolic body size. Sano et al (2004) reported that in sheep WBPS and WBPD were changed toward reduction with increased CP intake using both enrichments of plasma [1-13 C]Leu and a-[1-13 C]KIC.…”
Section: Discussionmentioning
confidence: 87%
“…Hyperinsulinaemic–euglycaemic–euaminoacidaemic clamp procedure Clamps were performed during steady feeding conditions achieved through 98% restricted 2 h feeding (Lapierre et al 1999; Thivierge et al 2002 b ). Hyperinsulinaemic – euglycaemic – euaminoacidaemic clamps were conducted according to the procedures described by Wray‐Cahen et al (1997).…”
Section: Methodsmentioning
confidence: 99%
“…Fed steady‐state whole‐body amino acid tracer kinetics followed by muscle biopsies l ‐[1‐ 13 C]Phenylalanine kinetics were conducted during steady nutritional intake of nutrients achieved through 98% restricted 2 h feedings (Lapierre et al 1999). The kinetics data are independent from those of the clamp and expand the response to LC n –3PUFA to a feeding‐induced stimulation.…”
mentioning
confidence: 99%
See 1 more Smart Citation